The equatorial counter electrojet: Part of a worldwide current system? - Gurubaran, S. (My University, 2002)
[1] The method of natural orthogonal components was applied to the ground geomagnetic data in the Central Asian sector (72–83°E), during the summer months of 1995, in an attempt to identify additional current systems that are superposed on the normal Sq current vortex and related to the equatorial counter electrojet (CEJ). The principal components, when examined in equivalent current representation, provide useful insights into the behavior of ionospheric current systems on different days. Statistical analyses performed in the present work suggest a possible relationship between the CEJ field and the noontime D variation observed at low latitudes. The results are in conformity with an earlier global simulation model.
Keywords: Equatorial counter electrojet; Sq current vortex; Magnetic observatories; CEJ field